Potential factors influencing lymphatic filariasis transmission in "hotspot" and "control" areas in Ghana: the importance of vectors - Sellase Pi-Bansa; Joseph Harold Nyarko Osei; Kwadwo Kyeremeh Frempong; Elizabeth Elhassan; Osei Kweku Akuoko; David Agyemang; Collins Ahorlu; Maxwell Alexander Appawu; Benjamin Guibehi Koudou; Michael David Wilson; Dziedzom Komi de Souza; Samuel Kweku Dadzie; et al. (BMC, 2019)
Abstract Background Mass drug administration (MDA) programmes for the control of lymphatic filariasis in Ghana, have been ongoing in some endemic districts for 16 years. The current study aimed to assess factors that govern the success of MDA programmes for breaking transmission of lymphatic filariasis in Ghana. Methods The study was undertaken in two "hotspot" districts (Ahanta West and Kassena Nankana West) and two control districts (Mpohor and Bongo) in Ghana. Mosquitoes were collected and identified using morphological and molecular tools. A proportion of the cibarial armatures of each species was examined. Dissections were performed on Anopheles gambiae for filarial worm detection. A questionnaire was administered to obtain information on MDA compliance and vector control activities. Data were compared between districts to determine factors that might explain persistent transmission of lymphatic filariasis. Results High numbers of mosquitoes were sampled in Ahanta West district compared to Mpohor district (F = 16.09, P = 0.002). There was no significant difference between the numbers of mosquitoes collected in Kassena Nankana West and Bongo districts (F = 2.16, P = 0.185). Mansonia species were predominant in Ahanta West district. An. coluzzii mosquitoes were prevalent in all districts. An. melas with infected and infective filarial worms was found only in Ahanta West district. No differences were found in cibarial teeth numbers and shape for mosquito species in the surveyed districts. Reported MDA coverage was high in all districts. The average use of bednet and indoor residual spraying was 82.4 and 66.2%, respectively. There was high compliance in the five preceding MDA rounds in Ahanta West and Kassena Nankana West districts, both considered hotspots of lymphatic filariasis transmission. Conclusions The study on persistent transmission of lymphatic filariasis in the two areas in Ghana present information that shows the importance of local understanding of factors affecting control and elimination of lymphatic filariasis. Unlike Kassena Nankana West district where transmission dynamics could be explained by initial infection prevalence and low vector densities, ongoing lymphatic filariasis transmission in Ahanta West district might be explained by high biting rates of An. gambiae and initial infection prevalence, coupled with high densities of An. melas and Mansonia vector species that have low or no teeth and exhibiting limitation.